USM PROUDLY SUPPORTS TWO RESEARCHERS ON ANTARCTICA EXPEDITION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 20 January 2016 - Two Universiti Sains Malaysia (USM) researchers,Dr. Foong Swee Yeok and Muhammad Hilal Mohd Zainudinwere among the eight researchers from six local universities who were on a 22-day expedition to Antarctica beginning 18 January, as a continuation of the involvement of Malaysian scientists in scientific expeditions which have started since 1999.